KOMUNIKASI STAKEHOLDER DALAM KEBIJAKAN NEW NORMAL PANDEMI COVID-19 DI SULAWESI TENGAH - Sulfitri Husain (KINESIK, 2022)
Communication is very crucial in answering and solving various problems. Since the Corona Virus Disease (Covid) epidemic in 2019, various policies have been made by the government to prevent and stop the spread of the virus which is also a global problem. The purpose of this study was to determine the involvement of stakeholders and their role in communicating new normal policies during the Covid-19 pandemic, especially in middle Sulawesi. Through qualitative descriptive research methods, the following research results were obtained: first, efforts to implement the new normal policy in middle Sulawesi involved several stakeholders, namely: local government, medical personnel, academics, and various parties including religious and community leaders. There are two communications used are; (1) formal communication through various policies to prevent the transmission of the new normal Covid, and (2) informal communication, with a face-to-face approach that is more humane to the community.